Adaptive cardiovascular hormones in a spectrum of heart failure phenotypes. (15th June 2015) - Zabarovskaja, Stanislava; Hage, Camilla; Linde, Cecilia; Daubert, Jean-Claude; Donal, Erwan; Gabrielsen, Anders; Mellbin, Linda; Lund, Lars H.
Abstract: Background/objectives: In heart failure (HF), activation of brain natriuretic peptide (BNP), atrial natriuretic peptide (ANP) and adrenomedullin (ADM) is adaptive. The activation of these peptides in relation to different HF phenotypes such as HF with preserved ejection fraction (HFpEF), reduced ejection fraction (HFrEF) and after left ventricular assist device (LVAD) and heart transplantation (HTx) remains poorly characterized. Methods: We measured and compared N-terminal (NT)-proBNP, mid-regional (MR)-proANP and mid-regional (MR)-proADM in 86 patients with HFpEF, 49 patients with HFrEF, 13 patients one year post-LVAD and 22 patients one year post-HTx. We assessed their prognostic impact using Kaplan–Meier analysis and multivariable Cox regression. Results: In HFpEF, HFrEF, LVAD and HTx, NT-proBNP, median (inter-quartile range), was 1000 (465–2335), 3145 (1475–5190), 1430 (986–2570), and 208 (127–353) pmol/L, p < 0.001. MR-proANP was 313 (192–381), 449 (325–596), 276 (216–305), and 118 (96–163) pmol/L, p < 0.001. MR-proADM was 1.2 (0.9–1.6), 1.3 (0.9–2.0), 0.9 (0.7–1.4), and 0.7 (0.6–0.9) nmol/L, p < 0.001 overall and p = 0.212 HFpEF versus HFrEF. In both HFpEF and HFrEF, NT-proBNP and MR-proANP predicted survival free from HTx or LVAD, independent of age, gender, NYHA class and eGFR, whereas MR-proADM did not. Conclusions: Patterns of the cardiomyocyte stress hormones NT-proBNP and MR-proANP suggest that compared to HFrEF, HFpEF may represent milder disease and LVAD and HTx may represent progressive resolution of HF severity. NT-proBNP and MR-proANP independently predicted prognosis in both HFpEF and HFrEF. In contrast, MR-proADM did not distinguish between HFpEF and HFrEF, did not predict prognosis in either, and may be more non-specific in HF.